Evaluation of ultraviolet‐C and spray‐drying processes as two independent inactivation steps on enterotoxigenic Escherichia coli K88 and K99 strains inoculated in fresh unconcentrated porcine plasma. (1st November 2018) - Blázquez, E.; Rodríguez, C.; Ródenas, J.; Pérez de Rozas, A.; Campbell, J.M.; Segalés, J.; Pujols, J.; Polo, J.
Abstract: The objectives of this study were to assess the effectiveness of an ultraviolet (UV‐C, 254 nm) irradiation system and the spray‐drying method as two independent safety steps on inactivation of Escherichia coli K88 and K99 spiked in porcine plasma at 6·46 ± 0·04 log10 ml −1 and 6·78 ± 0·67 log10 ml −1 respectively for UV‐C method, and at 7·31 ± 0·39 log10 ml −1 and 7·66 ± 0·11 log10 ml −1, respectively for the spray‐drying method. The UV‐C method was performed at different UV light doses (from 750 to 9000 J l −1 ) using a pilot plant UV‐C device working under turbulent flow. Spray‐drying treatment was done at inlet temperature 220 ± 1°C and two different outlet temperatures, 80 ± 1°C or 70 ± 1°C. Results indicated that UV‐C treatment induced a 4 log10 viability reduction for both E. coli at 3000 J l −1 . Full inactivation of both E. coli strains was achieved in all spray‐dried samples dehydrated at both outlet temperatures. The special UV‐C system design for turbid liquid porcine plasma is a novel treatment that can provide an additional redundant biosafety feature that can be incorporated into the manufacturing process for spray‐dried animal plasma. Significance and Impact of the Study: The safety of raw materials from animal origin such as spray‐dried porcine plasma (SDPP) may be a concern for the swine industry. Ultraviolet treatment at 254 nm (UV‐C) of liquid plasma has been proposed as an additional biosafety feature in the manufacturing process of SDPP. We found that UV‐C exposure in the liquid plasma at 3000 J l −1 reduces about 4 log10 ml −1 for E. coli K88 and K99. Full inactivation of both E. coli strains was achieved in all spray‐dried samples. The incorporation of UV‐C treatment to liquid plasma improves the robustness of the SDPP manufacturing process.